Gallipoli - Hart, Peter 1955- (Profile Books Ltd, 2011)
One of the most famous battles in history, Gallipoli forced Churchill from office, established Turkeys iconic founder Mustafa Kemal ('Ataturk') and marked Australias emergence as a nation in its own right